2014
DOI: 10.1177/0146167214538672
|View full text |Cite
|
Sign up to set email alerts
|

Political Conservatives’ Affinity for Obedience to Authority Is Loyal, Not Blind

Abstract: Liberals and conservatives disagree about obeying authorities, with conservatives holding the more positive views. We suggest that reactions to conservative authorities, rather than to obedience itself, are responsible for the division. Past findings that conservatives favor obedience uniformly confounded obedience with conservative authorities. We break down obedience to authority into its constituent parts to test the divisiveness of each part. The concepts of obedience (Study 1) and authority (Study 2) recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 31 publications
3
74
1
1
Order By: Relevance
“…We believe this is an important contribution because most research showing any convergence of liberal and conservative values has only been able to do so by altering the content of those values to match participants’ ideologies. For example, Frimer, Gaucher, and Schaefer () show that liberals and conservatives value authority equally, but only when deferring to authorities aligned with their ideology (e.g., liberals feel positively about obeying civil rights activists’ while conservatives feel positively about obeying commanding officers). Likewise, Frimer, Tell, and Motyl () show that liberals and conservatives both value sanctity, but only for ideology‐congruent issues (e.g., liberals value maintaining the purity of the environment; conservatives value maintaining the purity of traditional marriage).…”
Section: Discussionmentioning
confidence: 99%
“…We believe this is an important contribution because most research showing any convergence of liberal and conservative values has only been able to do so by altering the content of those values to match participants’ ideologies. For example, Frimer, Gaucher, and Schaefer () show that liberals and conservatives value authority equally, but only when deferring to authorities aligned with their ideology (e.g., liberals feel positively about obeying civil rights activists’ while conservatives feel positively about obeying commanding officers). Likewise, Frimer, Tell, and Motyl () show that liberals and conservatives both value sanctity, but only for ideology‐congruent issues (e.g., liberals value maintaining the purity of the environment; conservatives value maintaining the purity of traditional marriage).…”
Section: Discussionmentioning
confidence: 99%
“…This study joins a growing literature that suggests that liberals and conservatives are more alike in their moral functioning than previously thought. Like conservatives, liberals discriminate against outgroups (Wetherell, Brandt, & Reyna, ) and demand that other people obey their group's authorities (Frimer, Gaucher, & Schaefer, ). Like conservatives, liberals idolize leaders like Gandhi, Mother Teresa, and Martin Luther King, Jr. (Frimer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…More recent research on ideological differences in prejudice, intolerance, and authority obedience, however, have generated competing hypotheses and designed studies to allow for the possibility of arriving at the exact opposite conclusion (e.g., liberals are more intolerant, etc., e.g., Frimer, Gaucher, & Schaefer, 2014). This research found that yes, conservatives are more prejudiced against groups that pose perceived threats to cherished PROMOTING STRONG INFERENCES IN POLITICAL PSYCHOLOGY 7 conservative values (e.g., racial or sexual minorities).…”
Section: The Grid Approach To Hypothesis Testingmentioning
confidence: 76%
“…But liberals express similar levels of prejudice and discrimination against groups that violate their cherished values (e.g., pro-life advocates and Tea Party supporters, . Additionally, liberals and conservatives both have positive views about obeying authorities, once one takes into account whether the authority is generally perceived as a more liberal or conservative one (Frimer et al, 2014). Both groups are positive about obeying authorities that they see as representing their respective values.…”
Section: The Grid Approach To Hypothesis Testingmentioning
confidence: 99%